Analisis bahan ajar bahasa Indonesia bagi penutur asing “sahabatku Indonesia” untuk pelajar BIPA 1 - Syahfitri, Dian; Simbolon, Nova Tri Cahya Ramadhani; Padang, Nur Ridha Mamanda; Damanik, Novina Amelia (Education and Social Sciences Review, 2025)
The evaluation of Indonesian for speakers of other languages (BIPA) is important in the age of globalisation to ensure the effectiveness of learning for foreign speakers. This study attempts to evaluate the competence of the 2019 edition of the Sahabatku Indonesia course materials, the official published book for basic level (A1) learners, by analysing the suitability of the materials against the competence standards, the representation of Indonesian culture, and the quality of presentation. Using qualitative content analysis, this study examined the text, images, and audio of the teaching materials based on 16 indicators of Muslich's competency standards and Permendikbudristek No. 22 of 2022. The results show that these teaching materials fall into the excellent category with a feasibility percentage of 90.625%, excelling in pre-discourse, exercises and presentation of materials. However, there are inconsistencies in cultural representation, acronyms without explanation and outdated currency illustrations. The results confirm that adjustments should be made to these aspects to improve their relevance and effectiveness in BIPA materials, to ensure alignment with cultural development and learner needs, and to provide guidance for the development of more effective BIPA materials in the future.